Role of Free Prostate-Specific Antigen (f-PSA) in Modulating Gene Expression Involved in Prostate Tumor Growth - B. Bindukumar; Stanley A. Schwartz; Madhavan P. N. Nair; Ravikumar Aalinkeel; Elzbieta Kawinski; Kailash C. Chadha (Achievements and Challenges of Medicine and Medical Science Vol. 13, 2025)
Worldwide, prostate cancer (PCa) represents the second most common solid tumor in men. Prostate-specific antigen (PSA) is a serine protease that is widely used as a surrogate marker in the early diagnosis and management of prostate cancer. The present study examined the effect of enzymatically active f-PSA in modulating gene expression in prostate cancer cell lines using gene array analysis and real-time quantitative polymerase chain reaction (QPCR). The physiological relevance of tissue PSA levels and their role in prostate tumor growth and metastasis are not known. Free-PSA (f-PSA) was purified to homogeneity from human seminal plasma by column chromatography, eliminating hk2 and all known PSA complexes and retaining its protease activity. The final quantitation of PSA was based on double-determined enzyme-linked immunosorbent assay (ELISA) using polyclonal and monoclonal anti-PSA antibodies. The f-PSA was characterized for purity by SDS-PAGE/Western blot analysis using anti-PSA and anti-PSA complex monoclonal antibodies, and by 2-D gel electrophoresis with silver and antibody staining. Confluent monolayers of prostate cancer cell lines, PC-3M and LNCaP, were treated with f-PSA in a series of In vitro experiments to determine the changes in the expression of various genes that are known to regulate tumor growth and metastasis. Male athymic BALB/c nude mice, 5 weeks old, were used in the study. Gene array, quantitative polymerase chain reaction (QPCR), and enzyme-linked immunosorbent assay (ELISA) results show significant changes in the expression of various cancer-related genes in PC-3M and LNCaP cells treated with f-PSA. In a gene array analysis of PC-3M cells treated with 10 muM f-PSA, 136 genes were upregulated and 137 genes were downregulated. In LNCaP cells treated with an identical concentration of f-PSA, a total of 793 genes was regulated. QPCR analysis reveals that the genes for urokinase-type plasminogen activator (uPA), VEGF, and Pim-1 oncogene, known to promote tumor growth, were significantly downregulated, whereas IFN-gamma, known to be a tumor-suppressor gene, was significantly upregulated in f-PSA-treated PC-3M cells. The effect of f-PSA on VEGF and IFN-gamma gene expression and on protein release in PC-3M cells was distinctly dose-dependent. In vivo studies showed a significant reduction (P = .03) in tumor load when f-PSA was administered in the tumor vicinity of PC-3M tumor-bearing BALB/c nude mice. Our data support the hypothesis that f-PSA plays a significant role in prostate tumor growth by regulating various proangiogenic and antiangiogenic growth factors. This is the first observation to document that treatment of prostate cancer cells with f-PSA significantly modulates the expression of various growth factors involved in tumor growth. Such a change may be responsible for the suppression of the growth of prostate tumor xenograft in nude mice as observed. In view of the current findings that PSA may have tumor-protective activities in vivo, it is interesting to speculate that increased expression of PSA may also be an adaptive host antitumor response. Further research in this area is warranted.